Exploring the antecedents of coretax usage in tention: Evidence from perceptions of convenience, usefulness, and risk - Palullungan, Angelita; Duruk, Meichelle; Bangkaran, Tiara; Sabandar, Sita Y.; Pala'langan, Carolus Askikarno (Privietlab, 2026)
In the digital era, advances in information technology have prompted the Directorate General of Taxes (DGT) to reform the tax system through the Coretax Administration System, which will be launched in early 2025. This study aims to quantitatively analyze how perceived usefulness, perceived ease, and perceived risk influence taxpayers' intentions to use Coretax using a model-based approach, the Technology Acceptance Model (TAM). Data were obtained through the distribution of questionnaires to 100 respondents registered at the South Makassar Tax Office and analyzed using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS-SEM) with SmartPLS 4.0. The results of this study showed that the three independent variables of perceived usefulness, perceived ease of use, and perceived risk had a positive and significant effect on the use of Coretax